THE ASSOCIATION BETWEEN CAFFEINE CONSUMPTION AND DRY EYE DISEASE: A RETROSPECTIVE CROSS-SECTIONAL STUDY - Singh, Niharika; Singh, Arjun Kumar (Student's Journal of Health Research Africa, 2024)
Background Multifactorial dry eye disease (DED) results in ocular surface deterioration and instability of the tear film, which can lead to pain and problems in vision. Research on DED has contested coffee's effects on tear production and ocular surface health. The study investigated the connection between caffeine consumption and DED. Methods The Women's Health Research (WHS) dry eye questionnaire and data on caffeine consumption were completed by 500 research participants. After controlling for variables such as age, education level, sex, family income, body mass index (BMI), alcohol intake, smoking status, and medical comorbidities, multivariable logistic regression models were utilized to examine the relationship between caffeine intake and DED outcomes. Results 30% of people had DED as defined by the WHS, with females having a higher incidence (36.3%) than males (19.4%). Caffeine use was found to have a significant positive correlation with DED, with an increase in the odds of developing DED of 10% for every 100 mg/day of caffeine consumed (OR = 1.10, 95% CI = 1.02–1.18, p = 0.01). Females had a higher correlation with this (OR = 1.12, 95% CI = 1.03–1.21, p = 0.005). The risk of DED was further enhanced by inadequate sleep, high levels of work-related stress, and increased caffeine use. The main source of caffeine that was shown to be contributing to this risk was tea. Conclusion Higher caffeine intake is associated with an increased risk of DED, particularly among females and individuals with poor sleep quality or high work stress. Tea emerged as a significant contributor to this association. Recommendations The mechanisms underlying the link between caffeine use and DED require more investigation. Caffeine use should be moderated by public health standards to lower the risk of DED, particularly in more susceptible populations.